Pentraxin-3 - a promising biological marker in heart failure: literature review - Amina M. Alieva; Natalia V. Teplova; Maxim A. Batov; Kira V. Voronkova; Ramiz K. Valiev; Lidia M. Shnakhova; Tatiana V. Pinchuk; Alik M. Rakhaev; Marina R. Kalova; Igor G. Nikitin (ZAO "Consilium Medicum", 2022)
According to many studies, inflammation plays a very significant role in the pathogenesis of heart failure. Many studies have demonstrated an increase in circulating levels of inflammatory markers and cytokines such as C-reactive protein, tumor necrosis factor-a (TNF-a), and interleukins. C-reactive protein is produced in the liver in response to stimulation by various cytokines, mainly interleukin-6, and is a member of the pentraxin superfamily. Pentraxin-3, which is a long pentraxin, has a C-terminal domain of pentraxin similar to the classic short pentraxins, but differs from them in the presence of an unrelated long N-terminal domain. Various cell types can produce pentraxin-3 when exposed to primary inflammatory signals such as interleukin-1, tumor necrosis (TNF-a), oxidized low density lipoprotein, and microbial fragments (eg, lipopolysaccharide, lipoarabinomannans). Data in experimental animal models have demonstrated that pentraxin-3 can play cardioprotective and atheroprotective roles through its influence on the inflammatory process. Pentraxin-3 has been studied in several clinical protocols as a potential biomarker for cardiovascular disease.